Health and Healthcare Disparities: Impact on Resource Utilization and Costs After Transcatheter Aortic Valve Replacement. Issue 3 (May 2021) - Okoh, Alexis K.; Dhaduk, Nehal; Shah, Aakash M.; Gold, Justin; Fugar, Setri; Kassotis, John; Chen, Chunguang; Lee, Leonard Y.; Russo, Mark J.
Objective: We investigated health and healthcare disparities in the treatment of aortic stenosis with transcatheter aortic valve replacement (TAVR) and how they affect resource utilization and costs. Methods: We retrospectively reviewed all patients who were discharged alive after TAVR between 2012 and 2017 from the National Inpatient Sample. Patients were stratified by race and outcomes investigated were in-hospital complications, total procedural costs, and resource utilization. High resource utilization (HRU) was defined as length of stay (LOS) ≥7 days or discharge to a nonhome location. Multivariable regression models were used to identify predictors of HRU. Results: TAVR patients ( N = 29, 464) were stratified into Caucasians ( n = 25, 691), others ( n = 1, 274), Hispanics ( n = 1, 267), and African Americans (AA, n = 1, 232). More AA and Hispanics had TAVR at urban teaching centers ( P = 0.003) and were less likely to be Medicare beneficiaries ( P < 0.001). Distribution of TAVR patients in the lowest income quartile showed AA (50%) versus Caucasian (20%) versus Hispanic (33%, P < 0.001). In-hospital complications were higher among Hispanics and AA than Caucasians with prolonged LOS, procedural costs, and HRU. On multivariable analysis, independent predictors of HRU were TAVR year ( P < 0.001), advanced age ( P < 0.001), female sex ( P < 0.001), non-Caucasian race ( P = 0.038), history of coronary artery bypass grafting ( P < 0.001), smoking ( P < 0.001), chronic lung disease ( P = 0.003), stroke ( P < 0.001), and lowest income quartile ( P = 0.002). Conclusions: There exist significant healthcare and health disparities among patients undergoing TAVR in the United States. Consequently, this unequal access to care and determinants of heath translate into higher resource utilization and costs.